Pengaruh Persepsi Kemanfaatan Dan Kemudahan Penggunaan Terhadap Minat Pengguna Melalui Kepercayaan Menggunakan Layanan Mobile Banking - Kristina Novianti; Eka Bertuah (POLITEKNIK LP3I JAKARTA, 2023)
The use of technology at this time affects today's lifestyle, especially in the banking world, this development is reflected in the service system to customers in the form of mobile banking. Mobile Banking serves to make it easier for users to make transactions without the need to (ATM) or to the bank. There are 28 questions in this research questionnaire, so the minimum number of questionnaire samples required is 140 respondents. Sampling used in this population is purposive sampling. The data is then processed using Path Analysis. Based on the results of the research that has been done, it can be concluded that the perception of usefulness and the perception of convenience have a direct influence on trust. The better the perception of usefulness and the perception of convenience provided, the more user trust will increase. Then the user's interest is directly influenced by the perception of usefulness, the perception of convenience and trust, this means that with a good perception of usefulness and perception of convenience and a high sense of usertrust, it will increase the interest of users of mobile banking services. This means that they consider the benefits and convenience of mobile banking services in generating user interest, because they must be supported by trust in the perceived usefulness and convenience of mobile banking services as a service that can assist users in improving performance and effectiveness by transacting using mobile banking.Key words: Perceived Usefulness, Perception of Ease, Trust and User Interest